Fragile X tremor/ataxia syndrome: blame the messenger! - Swanson, M.S.; Orr, H.T. (Neuron, 2007)
rCGG repeats in premutant alleles of the fragile X gene (FMR1) cause neurodegeneration in Drosophila and are thought to cause fragile X-associated tremor/ataxia syndrome in humans. Two reports in this issue of Neuron (Jin et al. and Sofola et al.) present data indicating a disease mechanism involving disruption of RNA-binding protein function.